The Influence of Advertising Value towards the Purchase Intention of MORA.id’s Products - Tanuwijaya, Jessica; Gunawan, Lenny (Universitas Ciputra Surabaya, 2021)
MORA.id, a start-up beverage business, has been struggling to improve their advertisements and advertising value. Advertising value is considered to be an important factor to determine the consumers’ willingness to purchase advertised products or services. Hence, this research was conducted to analyze the influence of entertainment, informativeness, and irritation of advertising value towards the purchase intention of MORA.id’s products. To collect data for this research, the researcher used a census technique, and distributed questionnaires to all of MORA.id’s Instagram followers as the population. The distribution resulted a 69.51% return or 57 repondents, who were between the ages of 17 – 50 years old, followers of MORA.id’s Instagram profile, and are living in Indonesia. This research utilized SPSS 22 to process the collected data, and used multiple linear regression analysis to describe the influence of the 3 main independent variables towards the purchase intention. Based on the results of the multiple linear regression analysis, entertainment and informativeness were found to have significant influences towards the purchase intention. However, irritation was found to not have a significant influence towards the purchase intention. The data analysis also showed that entertainment, informativeness, and irritation were found to have a positive correlation with the purchase intention.